1980
DOI: 10.2466/pr0.1980.46.2.583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Apprehension about Writing to Performance as Measured by Grades in a College Course on Composition

Abstract: A questionnaire on the measurement of apprehension about writing was given to 1,257 students enrolled in their first college course in composition. Scores on the questionnaire did not correlate well with a measure of performance, grades in the composition course. A general measure of verbal facility and skills, Composite American College Test scores, correlated well with grades. These findings raise questions about what is measured by the questionnaire and suggest that achievement in writing depends more heavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Previous research has shown that students with higher anxiety received lower grades on essays, written exams, and standardized writing tests (Daly, 1985;Lee & Krashen, 1997). However, Fowler and colleagues (Fowler & Kroll, 1980;Fowler & Ross, 1982) found no significant relationship between writing anxiety and grades, particularly when English proficiency was controlled. Other studies indicated that students in advanced writing classes reported lower writing anxiety (Daly & Miller, 1975; • H1-Students with higher GPAs experience lower levels of writing anxiety than students with lower GPAs.…”
Section: Writing Self-efficacymentioning
confidence: 95%
“…Previous research has shown that students with higher anxiety received lower grades on essays, written exams, and standardized writing tests (Daly, 1985;Lee & Krashen, 1997). However, Fowler and colleagues (Fowler & Kroll, 1980;Fowler & Ross, 1982) found no significant relationship between writing anxiety and grades, particularly when English proficiency was controlled. Other studies indicated that students in advanced writing classes reported lower writing anxiety (Daly & Miller, 1975; • H1-Students with higher GPAs experience lower levels of writing anxiety than students with lower GPAs.…”
Section: Writing Self-efficacymentioning
confidence: 95%
“…This lack of effect may in part be the result of the small sample and overall low level of self-reported writing apprehension. However, Fowler and Kroll (1980) raised questions about what is measured by the WAT and whether it was the appropriate measure to use when evaluating writing achievement. A more sensitive measure of writing ability or confidence may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Shang's (2012) study also revealed that students became nervous when asked to write an English composition in class because they feared for making mistakes in language forms (e.g., grammar and vocabulary). While a large body of research (Aida, 1994;MacIntyre & Gardner, 1991a) shows a negative relationship between anxiety and actual proficiency, Fowler and Kroll (1980) found no relationship between writing anxiety and grades in a college writing class. Except the inconsistent results regarding the relationship between anxiety and actual achievement, gender-related anxiety research has yielded conflicting results.…”
Section: Introductionmentioning
confidence: 94%